Factors Associated With the Improvement of Left Ventricular Systolic Function by Continuous Positive Airway Pressure Therapy in Patients With Heart Failure With Reduced Ejection Fraction and Obstructive Sleep Apnea - Naito, Ryo; Kasai, Takatoshi; Dohi, Tomotaka; Takaya, Hisashi; Narui, Koji; Momomura, Shin-ichi (Frontiers in Neurology, 2022)
Background Obstructive sleep apnea (OSA) is a potential risk factor in cardiovascular diseases, including arrhythmia, coronary artery disease, and heart failure (HF). Continuous positive airway pressure (CPAP) therapy is an effective therapy for OSA and the underlying HF, partly through a 5–9% increase in the left ventricular ejection fraction (LVEF). However, the data on the factors associated with the efficacy of CPAP on LVEF in patients with HF complicated by OSA are scarce. This study aimed to investigate whether LVEF improves in patients with OSA and HF after 1 month of CPAP therapy, and to clarify which factors are associated with the degree of LVEF improvement. Method This was a prospective, single-arm, open-label study. We enrolled moderate-to-severe patients with OSA and HF who were being followed up at the cardiovascular center of Toranomon Hospital (Tokyo, Japan). The parameters of sleep study and LVEF were assessed at the baseline and after 1 month of CPAP. The multivariate regression analyses, with changes in LVEF as a dependent variable, were performed to determine the factors that were associated with the degree of LVEF improvement. Results We analyzed 55 consecutive patients with OSA and HF (mean age: 60.7 ± 12.2 years, mean LVEF value: 37.2 ± 9.8%). One month of CPAP treatment decreased the apnea-hypopnea index (AHI) from 45.3 ± 16.1 to 5.4 ± 4.1 per hour, and the LVEF improved from 37.2 ± 9.8 to 43.2 ± 11.7%. The multivariate regression analyses demonstrated that age and body mass index (BMI) were significant determinants of LVEF improvement. Conclusion The LVEF improved significantly after 1 month of CPAP therapy in Japanese patients with OSA and HF. Multivariate regression analyses indicated that an improvement in LVEF was likely to be observed in young patients with obesity.